Socio-Economic Development Through Agro- Tourism: A Case Study Of Bhaktapur, Nepal - Pandey, Hemprabha; Pandey, Pradyumna Raj (Journal of Agriculture and Environment, 2013)
Socio-economic development of Nepal relies on harnessing the potentials of tourism, handicrafts, non-timber forests, and high-value low-volume agricultural products, and human resources. Tourism and agriculture in Nepal are major elements in this development, acting as revenue generating industries with multiplier effects on the economy and significant employment capacity, which significantly contributes to GDP and rural income generation. Among the mid hill districts of Nepal, Bhaktapur maintains a high potential to benefit from the synergism between tourism, agro-farming, and handicrafts, giving it the internal elements necessary for socio-cultural development. As Bhaktapur has already been included in the list of UNESCO World Heritage Sites, protection and renovation of ancient artistic monuments is essential. For the sustainable development of tourism and agro-eco tourism in Bhaktapur, as well as an umbrella policy of guidelines accompanied by national laws are to be formulated and implemented through communitybased management. In this way Bhaktapur can contribute to the long standing Nepalese desire for a nation building process by utilizing the competitive and comparative advantages of tourism and agriculture opportunities available in the district. The Journal of Agriculture and Environment Vol:12, Jun.2011, Page 59-66 DOI: http://dx.doi.org/10.3126/aej.v12i0.7564